2021
DOI: 10.2478/sm-2021-0019
|View full text |Cite
|
Sign up to set email alerts
|

Plesionyms as a Vocabulary Teaching Tool: The Case of Estonian EFL Learners

Abstract: Summary The present study investigated the effectiveness of using plesionyms, or near-synonyms, as a vocabulary teaching tool in the English as a foreign language classroom and attempted to determine at what level of proficiency this technique could be incorporated. 40 Estonian university students who were enrolled in three different ESP courses participated in the study. The students were divided into 4 groups according to their level of proficiency: one experimental and one control group consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Interestingly, near-synonyms can also be used as a vocabulary teaching technique on their own. Previous research has demonstrated that teaching vocabulary through pairs of near-synonyms is beneficial for long term memory retention at advanced levels of proficiency in particular (Yevchuk 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, near-synonyms can also be used as a vocabulary teaching technique on their own. Previous research has demonstrated that teaching vocabulary through pairs of near-synonyms is beneficial for long term memory retention at advanced levels of proficiency in particular (Yevchuk 2021).…”
Section: Introductionmentioning
confidence: 99%